Analisis Hukum Terhadap Sengketa Hak Pengelolaan Antara PT Sari Dewi Membangun dengan Pemerintah Kota Palu - Widyatmi Anandy; Irzha Friskanov S (Res Judicata, 2022)
Management rights are the controlling rights of the State whose implementing authority is partially devolved to the holder, such authority includes the authority to use the land for its business purposes and hand over parts of the land to third parties. There are problems in the transfer of land rights over land management rights as well as legal settlement efforts to solve the problem of land transfer. This problem of state land management then gives rise to a separate right, namely the right to state land management. PT Sari Dewi Membangun with the Palu City Government. The problem to discuss it is how to analyze the legal analysis of the management rights dispute between PT Sari Dewi Membangun and the Palu City Government. This research was conducted by research methods with empirical juridical analysis. By using a general foundation race on the Theory of Legislation, the Theory of Authority and Government Action. As well as identifying with a statutory and conceptual approach. The transfer of rights to management land carried out without the consent of the holder of the Management Right cannot be said to be valid according to law, it is determined that any transfer of the use of land that is part of the management rights land to a third party by the holder of the management right, whether accompanied or not accompanied by the erection of buildings on it, must be carried out by making a written agreement between the party holding the management right and the third party that  Concerned.